Pharmacognostical and Pharmaceutical Assay of Treesa Haritaki Terminalia chebula Retz - Joshi, Shivam (International Journal of Pharmaceutical & Biological Archive, 2014)
Pharmacognostical and Pharmaceutical Assay of Treesa Haritaki Terminalia chebula Retz